Mucin 2 silencing promotes colon cancer metastasis through interleukin-6 signaling - Hui-Ping Hsu (Nature Portfolio, 2017)
Abstract Downregulation of Mucin 2 (MUC2) expression is associated with early carcinogenesis events in colon cancer. MUC2 plays a role in the progression of colon cancer, and reduced MUC2 protein expression correlates with increased interleukin-6 (IL-6) expression. However, the interaction between MUC2 and IL-6 in colorectal cancer metastasis remains unclear. We systematically analyzed MUC2 and IL-6 expression and determined the survival of cancer patients with high or low MUC2 and IL-6 expression using the Oncomine and PrognoScan databases, respectively. This analysis identified downregulation of MUC2 and overexpression of IL-6 in colon cancer but not in normal colon tissue, and this expression pattern was correlated with poor survival of colon cancer patients. We examined the effects of MUC2 on colon cancer metastasis and used vector-mediated application of short hairpin RNA (shRNA) to suppress MUC2 expression. MUC2 suppressed the migration of colon cancer cells in vitro and dramatically diminished liver metastases in vivo. Treatment with IL-6 increased signal transducer and activator of transcription 3 (STAT3) phosphorylation, promoted checkpoint kinase 2 (Chk2) activation, attenuated cAMP response element-binding protein (CREB) phosphorylation, and suppressed E-cadherin protein expression in MUC2-silenced HT-29 cancer cells. Most importantly, MUC2 is a potential prognostic indicator for colon cancer.